Management of Intestinal Injury in Deployed UK Hospitals. Issue 4 (1st December 2011) - Fries, Cdr Anton; Penn-Barwell, J; Tai, NRM; Hodgetts, TJ; Midwinter, MJ; Bowley, DM
Abstract : Introduction: Definitive laparotomy (DL), with completion of all surgical tasks at first laparotomy has traditionally been the basis of surgical care of severe abdominal trauma. Damage control surgery (DCS) with a goal of physiological normalisation achieved with termination of operation before completion of anatomical reconstruction, has recently found favour in management of civilian trauma. This study aims to characterise the contemporary UK military surgeon's approach to abdominal injury. Patients and methods: A retrospective analysis was performed on British service personnel who underwent a laparotomy for intestinal injury at UK forward hospitals from November 2003 to March 2008 as identified from the Joint Theatre Trauma Registry. Patient demographics, mechanism and pattern of injury and clinical outcomes were recorded. Surgical procedures at first and subsequent laparotomy were evaluated by an expert panel. Results: 22 patients with intestinal injury underwent laparotomy and survived to be repatriated; all patients subsequently survived to hospital discharge. Mechanism of injury was GSW in seven and blast in 13. At primary laparotomy, as defined by the operating surgeon, 15/22 underwent DL and 7/22 underwent DCS. Mean Injury Severity Score (ISS) was 19 for DL patients compared to 29 for DCS patients (p=0.021). Of the 15 patients undergoing DL nine had primary repair (suture or resection / anastomosis), one of which subsequently leaked. Unplanned re-look was required in 4/15 of the DL cases. Conclusion: This review examines the activity of British military surgeons over a time period where damage control laparotomy has been introduced into regular practice. It is performed at a ratio of approximately 1:2 to DL and appears to be reserved, in accordance with military surgical doctrine, for the more severely injured patients. There is a high rate of unplanned relook procedures for DL suggesting DCS may still be underused by military surgeons. Optimal methods of selection and implementation of DCS after battle injury to the abdomen remain unclear.